2018
DOI: 10.1140/epjp/i2018-12409-y
|View full text |Cite
|
Sign up to set email alerts
|

Fate of a thin-shell wormhole powered by Morris-Thorne wormhole

Abstract: Asymmetric thin-shell wormholes from two traversable Morris-Thorne wormhole spacetimes, with identical shape but different redshift functions, are constructed. Energy density of the thin-shell wormhole derives its power from a Morris-Thorne wormhole which is already exotic. By choice, the weak energy condition for the thin-shell wormhole is satisfied. A linear barotropic equation of state is assumed to hold after the radial perturbations. The fate of our thin-shell wormhole, after the perturbation, is striking… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…Forghani et al. [ 53 ] formulated asymmetric thin‐shell from two traversable WHs with different redshift functions by assuming barotropic EoS. They analyzed that either thin‐shell collapses to the original wormhole or expands along shell's radius.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forghani et al. [ 53 ] formulated asymmetric thin‐shell from two traversable WHs with different redshift functions by assuming barotropic EoS. They analyzed that either thin‐shell collapses to the original wormhole or expands along shell's radius.…”
Section: Introductionmentioning
confidence: 99%
“…Garcia et al [52] investigated stability of thin-shell established from the wormhole geometries using cut and paste procedure and found that exotic matter has significant effects on stable configuration. Forghani et al [53] formulated asymmetric thin-shell from two traversable WHs with different redshift functions by assuming barotropic EoS. They analyzed that either thin-shell collapses to the original wormhole or expands along shell's radius.…”
Section: Introductionmentioning
confidence: 99%
“…Note that, the coordinates of the two sides of the throat x µ ± , and more generally, the very nature of the two spacetimes does not necessarily need to be the same. Although most of the authors have been tending to consider same spacetimes as the side manifolds, recently such a mirror symmetry was broken in some studies [19][20][21] to introduce ATSWs.…”
Section: Constructing a Tswmentioning
confidence: 99%
“…Using a cut-and-paste method, Garcia et al [52] studied the stability of thin-shell structures derived from WH geometries and discovered that exotic matter significantly affects stable configuration. By assuming barotropic EoS, Forghani et al [53] developed an asymmetric thin-shell from two traversable WHs with various redshift functions. By merging a traversable WH with standard BHs (Bardeen and Hayward BHs), Sharif and Ashraf [54] created athin-shell structure and studied its stability as well as dynamics.…”
Section: Introductionmentioning
confidence: 99%